Émergence d'une Église fraternelle et synodale en Chine: Analyse théologique d'une enquête auprès de jeunes catholiques en Chine - Lepeu, Bruno (Revue théologique de Louvain, 2025)
Based on his thesis work on what is emerging in the Church in China, the author presents the interest of an ecclesiology starting from the action of the People of God and the theological insights gained from analyzing his corpus of interviews with young Catholics engaged in the Church in China, resonating with the Acts of the Apostles (I). Relying on the essential role played by fraternal ecclesial communities in the process of faith appropriation by young people, the author develops a figure of the Church-Fraternity founded on the patristic theology of Christ the Brother (II), which anchors synodality in fraternity (III).